Substance Use Patterns of Gay and Bisexual Men in the Momentum Health Study. Issue 5 (September 2018) - Roth, Eric Abella; Cui, Zishan; Wang, Lu; Armstrong, Heather L.; Rich, Ashleigh J.; Lachowsky, Nathan J.; Sereda, Paul; Card, Kiffer G.; Jollimore, Jody; Howard, Terry; Olarewaju, Gbolahan; Moore, David M.; et al.
Research with male sexual minorities frequently combines gay and bisexual men as Men Who Have Sex with Men or Gay and Bisexual Men. When analyzed separately, bisexual men consistently feature negative health differentials, exemplified by higher substance use levels. This interpretation is not clear-cut because studies may combine bisexual men and women, use different dimensions of sexual orientation to define bisexuality, and/or not consider number of sexual partners as a possible confounding factor. This study conducted separate bivariate and multivariate analyses comparing gay to bisexual Momentum Study participants based on self-identity, sexual attraction, and sexual behavior, while controlling for number of sexual partners and sociodemographic, psychosocial, and sexual behavior measures. The study hypothesized that, regardless of definition, bisexual men feature higher substance use levels compared to gay men. Bivariate analyses revealed significantly higher ( p < .05) use among bisexual men for multiple substances in all samples. Nonprescription stimulants and heroin were significant in all multivariate logistic regression models. In contrast, all bisexual samples reported lower use of erectile dysfunction drugs and poppers, substances associated with anal sex among gay men. Subsequent analysis linked these results to lower levels of anal sex in all bisexual samples. Bivariate analyses also revealed that bisexual men featured significantly lower educational levels, annual incomes, and Social Support Scales scores and higher Anxiety and Depression Sub-Scale Scores. In summary, findings revealed bisexual men's distinctive substance use, sexual behavior, psychosocial, and sociodemographic profiles, and are important for tailoring specific health programs for bisexual men.